Exploring the NANOG-TET2 interaction interface. Effects of a selected mutation and hypothesis on the clinical correlation with anemias - Testi, Claudia; Piacentini, Roberta; Perrone, Alessandro; Bartoli, Chiara; Leso, Daniele; Pavia, Domitilla; Pistolesi, Elisa; Scipione, Flavio; Cotronea, Irene; Adinolfi Falcone, Marco; Ierani, Marco; Boffi, Alberto; et al. (Frontiers in Chemical Biology, 2025)
In this study, we focused on the computational analysis of a selected single-point mutation identified by a NGS screening panel in the TET2 enzyme classified as “variant of uncertain clinical significance.” The mutation, namely Q1084P, occurs at the interface between TET2, an important epigenetic regulator, and NANOG, a transcription factor fundamental for hematopoietic cells differentiation. Notably, the mutation occurs in a protein region distant from the active site; moreover, the experimental structures of the interacting region of both proteins are unknown, making it difficult to validate the impact of TET2 mutation on its binding with NANOG. To address these challenges, we employed an integrated computational approach combining molecular docking, molecular dynamics simulations and protein-protein interaction prediction. Our findings indicate that the single-point mutation might effectively reduce the TET2-NANOG interaction, which would consequently impair cells differentiation and hematopoiesis process, consistent with the clinical presentation of pure red cell aplastic anemia. These results, along with the proposed computational method, provide insights for establishing clinical correlations between variants of uncertain significance and anemias in general, comprising common hematological problems widespread in the world population and for which dedicated NGS panels are still not available.